Comparative evaluation of the influencing effects of geomagnetic solar storms on earthquakes in anatolian peninsula (2009)
Earthquakes are tectonic events that take place within the fractures of the earth's crust, namely faults. Above certain scale, earthquakes can result in widespread fatalities and substantial financial loss. In addition to the movement of tectonic plates relative to each other, it is widely discussed that there are other external influences originate outside earth that can trigger earthquakes. These influences are called "triggering effects". The purpose of this article is to present a statistical view to elaborate if the solar geomagnetic storms trigger earthquakes.As a model, the research focuses on the Anatolian peninsula, presenting 41 years of historical data on magnetic storms and earthquakes collated from national and international resources. As a result of the comparative assessment of the data, it is concluded that the geomagnetic storms do not trigger earthquakes.